The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5114/pdia.2014.43191
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety of antihistamines

Abstract: Histamine is a mediator, which increases the permeability of capillaries during the early phase of allergic reaction, causes smooth muscle contraction of bronchi and stimulates mucous glands in the nasal cavity. Antihistamines are the basis of symptomatic treatment in the majority of allergic diseases, especially allergic rhinitis, allergic conjunctivitis, urticaria and anaphylaxis. The cardiotoxic effects of the two withdrawn drugs, terfenadine and astemizole, were manifested by prolonged QT intervals and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…However, it has already been withdrawn from the market due to the cardiotoxicity effect [21]. During electrocardiogram (ECG) detection in human patients, astemizole displayed long QT intervals, arrhythmia that triggered torsades de pointes, and caused sudden death [22]. We observed that embryonic zebrafish changed the cardiac rhythm within 1 hour after being treated with 5 µM astemizole by an endpoint evaluation method (see Video S1 for wild-type and Video S2 for astemizole-treated embryos).…”
Section: Endpoint Methods Of Astemizole Incubationmentioning
confidence: 94%
“…However, it has already been withdrawn from the market due to the cardiotoxicity effect [21]. During electrocardiogram (ECG) detection in human patients, astemizole displayed long QT intervals, arrhythmia that triggered torsades de pointes, and caused sudden death [22]. We observed that embryonic zebrafish changed the cardiac rhythm within 1 hour after being treated with 5 µM astemizole by an endpoint evaluation method (see Video S1 for wild-type and Video S2 for astemizole-treated embryos).…”
Section: Endpoint Methods Of Astemizole Incubationmentioning
confidence: 94%
“…174 Ebastine and mizolastine also need to be used with caution in those with cardiac risk factors, 175 but even cetirizine, desloratadine, diphenhydramine, fexofenadine, loratadine were possibly associated with cardiac arrhythmias in a single large European pharmacovigilance study. 174 Ebastine and mizolastine also need to be used with caution in those with cardiac risk factors, 175 but even cetirizine, desloratadine, diphenhydramine, fexofenadine, loratadine were possibly associated with cardiac arrhythmias in a single large European pharmacovigilance study.…”
Section: Second-generation Antihistaminesmentioning
confidence: 99%
“…Terfenadine and astemizole were implicated in deaths from ventricular fibrillation via QT interval prolongation. 174 Ebastine and mizolastine also need to be used with caution in those with cardiac risk factors, 175 but even cetirizine, desloratadine, diphenhydramine, fexofenadine, loratadine were possibly associated with cardiac arrhythmias in a single large European pharmacovigilance study. 176 Interaction with other medications is rare other than for mizolastine with certain anti-arrhythmics, antibiotics and beta-blockers leading to an increased risk of arrhythmia.…”
Section: Second-generation Antihistaminesmentioning
confidence: 99%
“…In some cases, in particular the mentioned antihistamines, inhibition of their CYP3A4‐mediated metabolism by several drugs (e.g., macrolides like erythromycin, azole antimycotics such as itrakonazole and ketokonazole) increased the plasma concentration of them with subsequent blockade of the I Kr current and markedly increased risk of torsade de pointes. A similar situation is encountered in persons with reduced metabolic capacity due to liver diseases …”
Section: Drugs With the Major Effects On The Heartmentioning
confidence: 68%
“…A similar situation is encountered in persons with reduced metabolic capacity due to liver diseases. [265][266][267][268] The relationship between QT interval prolongation and the incidence of torsade de pointes is not direct. 261,262,269 Also, QT prolongation is not a uniform condition (see Fig.…”
Section: Potassium Channelsmentioning
confidence: 99%